キョクイキ チュウソウ タイキ リキガク ノ モンダイテン ト カンソク ヘノ ヨウセイ f. キョクイキ デンリソウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 廣田, 勇; ヒロタ, イサム; HIROTA, Isamu (1980)
P(論文) MAP期間中に,南極大陸で行われる中層大気観測の計画作成にひとつの指針を与える目的で,極域中層大気循環に関する現在の知識と理解を簡単に概観する.中層大気中の大規模運動は,夏冬両極の熱冷源により駆動されている.したがって,極域における循環の様相は夏と冬の季節別の特徴が著しく異なっている.一方,南北面半球の非対称性も無視できない.従来の限られた観測結果から見ると,この差異は特に波動の卓越する冬期に大きい.これらの問題を念頭に置き,近い将来,衛星,ロケット等により極域中層大気の観測を行う際に,それらの観測手段の長短を認識した上で最適の観測プログラムを作るべきことを述べる. A brief discussion is made on the structure and dynamics of the polar middle atmosphere. It is pointed out that the difference between the northern and southern hemispheres is largest in winter in the polar region for both the mean structure and planetary waves. 0n the basis of this consideration, an emohasis is placed on the need of making the well-coordinated observation program in Antarctica during the MAP period. departmental bulletin paper